Synthesis of Multisensory Space to Support Literacy of Children with Dyslexia: A Literature Study-Based Approach - Danielle Arum; Anisza Ratnasari (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2026)
Dyslexia as a neurobiological learning disorder poses significant challenges to children’s literacy development, particularly in phonological processing, memory, and symbol recognition. These challenges require learning approaches that are cognitively adaptive, meaning strategies that align instructional methods with children’s sensory processing and information processing mechanisms, as well as support from physically responsive learning environments. One widely discussed approach is multisensory learning, which integrates visual, auditory, tactile, and kinesthetic stimuli in the learning process. Although multisensory approaches have been extensively explored in pedagogical contexts, their translation into architectural design for learning spaces remains insufficiently synthesized. This gap highlights the need to systematically connect learning activities with spatial design implications. Therefore, this study aims to identify the relationships between dyslexic characteristics, multisensory learning activities, and their implications for physical learning space requirements. This research adopts a qualitative descriptive approach through a literature-based study, employing thematic analysis to map relationships between types of sensory stimuli, forms of learning activities, and corresponding spatial needs. The findings indicate that multisensory approaches have strong potential to support literacy processes by activating multiple sensory pathways. The resulting synthesis produces a typology of spatial functions, including tactile zones (e.g., sand/textured areas), interactive creative rooms, auditory spaces, and movement-based outdoor environments. Rather than empirically testing effectiveness, this study proposes a conceptual framework that links multisensory activities with spatial design strategies, contributing to the development of more inclusive and responsive learning environments for children with dyslexia